1977
DOI: 10.1111/j.1476-5381.1977.tb07732.x
|View full text |Cite
|
Sign up to set email alerts
|

The PHARMACOLOGY OF ADRENERGIC NEURONAL RESPONSES IN THE CEREBRAL CORTEX: EVIDENCE FOR EXCITATORY Α‐ AND INHIBITORY Β‐RECEPTORS

Abstract: It is concluded that (a) responses of cortical neurones to adrenoceptor agonists are mediated by both a-and /-receptors; (b) these a-and /3-receptors give rise to opposite effects: the a-receptors being excitatory and the /3-receptors being inhibitory; and (c) responses of many neurones reflect the presence of both types of receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(41 citation statements)
references
References 14 publications
6
35
0
Order By: Relevance
“…In contrast, higher doses of NE suppressed both spontaneous and evoked activity in NIf and HVC. These results agree well with previous data from mammalian studies suggesting a dose-dependent enhancement and suppression of cortical responsiveness by local NE application (Bevan et al, 1977;Rogawski and Aghajanian, 1980;Waterhouse et al, 1981Waterhouse et al, , 1982Armstrong-James and Fox, 1983;Mouradian et al, 1991;Pralong and Magistretti, 1995). The dose-dependent effects of NE in NIf suggest that neuromodulatory input to NIf may dynamically regulate the flow of auditory information to the rest of the song system.…”
Section: Noradrenergic Effects On Sensory Responsivenesssupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, higher doses of NE suppressed both spontaneous and evoked activity in NIf and HVC. These results agree well with previous data from mammalian studies suggesting a dose-dependent enhancement and suppression of cortical responsiveness by local NE application (Bevan et al, 1977;Rogawski and Aghajanian, 1980;Waterhouse et al, 1981Waterhouse et al, , 1982Armstrong-James and Fox, 1983;Mouradian et al, 1991;Pralong and Magistretti, 1995). The dose-dependent effects of NE in NIf suggest that neuromodulatory input to NIf may dynamically regulate the flow of auditory information to the rest of the song system.…”
Section: Noradrenergic Effects On Sensory Responsivenesssupporting
confidence: 83%
“…The results of the present study are somewhat similar to those observed in mammalian systems, in which noradrenergic enhancement of responses is primarily the result of ␣ 1 receptor activation and suppressive effects have variously been shown to result from ␣ 2 receptor activation, higher levels of ␣ 1 receptor activation, and ␤ receptor-dependent enhancement of inhibitory synaptic transmission (Bevan et al, 1977;Rogawski and Aghajanian, 1980;Waterhouse et al, 1981Waterhouse et al, , 1982; Armstrong-James and Fox, 1983; Mouradian et al, 1991; Pralong and Magistretti, 1995; Devilbiss and Waterhouse, 2000). Although the data presented here suggest that ␣ 1 and ␣ 2 adrenergic receptors in NIf are involved in the modulation of activity in NIf and HVC, it is still unknown whether NE is acting directly on projection neurons, indirectly via local inhibitory interneurons, or both.…”
Section: Noradrenergic Effects On Sensory Responsivenesssupporting
confidence: 75%
“…Intervals between successive applications of the same agonist were kept constant in order to standardize the effects of the retaining current upon drug release during the ejection period (Bradshaw et al, 1973a, b). The effects of antagonists were evaluated by the procedures described previously (Bevan et al, 1977; Effects of haloperidol on excitatory responses to dopamine and DPI The effects of haloperidol were examined on 11 cortical neurones excited by both dopamine and DPI. On every cell studied acetylcholine (ACh) was used as a control agonist.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence indicates that these responses are mediated by pharmacologically distinct receptors: the excitatory responses by a-adrenoceptors, and the depressant responses by ,B-adrenoceptors (Bevan, Bradshaw & Szabadi, 1977). Dopamine, like NA, can both excite and depress cortical neurones (Bevan, Bradshaw & Szabadi, 1975;Stone, 1976;Bunney & Aghajanian, 1976;Sharma, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of this drug appear to be dosedependent and may also involve actions on both preand post-synaptic monoamine sites. (Bevan, Bradshaw & Szabadi, 1976). Cortical neurones are also sensitive to dopamine (DA), both excitatory and depressant responses having been described (Bevan, Bradshaw & Szabadi, 1975;Stone, 1976 Recently, Kitai, Sugimoro & Kocsis (1976) suggested that the depressant action of dopamine in the striatum might be due to an excitation of inhibitory interneurones.…”
Section: We Wish To Thank the Medical Research Council Fisonsmentioning
confidence: 99%